Vocational needs of the educable mentally retarded children in selected schools in Metro Manila - Panesa, Paz Mercedes L.; Baldo, Trinidad C. (aQuezon City College of Education, University of the Philippines Diliman, 1986)
This study sought to find out the vocational needs of the educable mentally retarded (EMR) learners in selected schools in Metro Manila as perceived by five groups of respondents.
Typescript.
Thesis (Master of Education - Special Education)--University of the Philippines, Diliman
Keywords: Mentally handicapped children -- Education. -- Philippines -- Manila metropolitan area